Non classical function of vitamin d – influence on reproductive health, puberty and fertility - Chaykivska, Elina; Chaykivska, Zlata (REPRODUCTIVE ENDOCRINOLOGY, 2014)
In the past few years, there has been growing appreciation for the many roles of vitamin D and its active metabolites in a large number of tissues. Most tissues in the body, not just those participating in the classic action of vitamin D such as bone, kidney and gut, have receptors (VDR) for the active form of vitamin D – 1,25 dihydroxyvitamin D. The recent data on vitamin D from retrospective, prospective observational studies, case-control and experimental studies confirm the essential role of vitamin D in a variety of physiological functions. Last time there has been growing interest in this substance observed in the scientific researches and biomedical literature, due to findings which demonstrate a vitamin D deficiency status in the population. This review is an analysis of the association between the vitamin D and the female and male reproduction and fertility. We highlight the latest findings from medical trials on vitamin D during last years. The aim of this article is to understand how vitamin D affects the female and male fertility. Vitamin D is a hormone which controls nearly 1/3 of human and mice genome, over 200 genes in a human body, including those responsible for cell cycle control: proliferation, differentiation, apoptosis. Apart from basic functions, which are maintaining calcium-phosphoric balance, vitamin D takes active part in process of cell proliferation, epidermal keratinocyte differentiation, immune system stimulation, insulin secretion, brain metabolism, adipocytes function, puberty, reproduction and fertility. The vitamin D receptors (VDR) and vitamin D metabolizing enzymes are found in reproductive tissues of women and men. VDR knockout mice have significant gonadal insufficiency, decreased sperm count and motility, and histological abnormalities of testis, ovary and uterus. Assuming that 30 ng/ml (75 nmol/l) is a lower limit of normal concentration of 25(OH)D3 in serum, the number of people with vitamin D deficit equals about 1 billion worldwide.